Variações genéticas nos genes do inflamassoma e o câncer colorretal : implicações prognósticas - Cambui, Raylane Adrielle Gonçalves (2019)
Colorectal cancer (CRC) is the second most common tumor in the world and one of the leading causes of cancer-related death. Loss of intestinal mucosal homeostasis as well as exacerbate and/or chronic gut inflammation have been demonstrated to be prominent susceptibility triggers. Due to the ability to mediate inflammation, several studies have been focusing on elucidating the role of inflammasome complex in tumor development. Experimental models of multifactorial pathologies in mice have revealed the importance of the inflammasome in the RCC, but there is still a shortage of studies with humans. Taking into account that genetic variants in inflammatory components have previously been associated with inflammatory bowel diseases (IBD), as well as carcinogenesis and/or tumor prognosis, it is justifiable the development of researches aiming to elucidate the contribution of the genetics of the inflammasome in the CRC. In this document, it is first proposed a bibliographical review on the topic mentioned above, followed by the presentation of results from an experimental research, in an article format, that aimed to evaluate the influence of polymorphisms in the inflammasome gene and its components in a cohort of 215 individuals with CRC who were followed for at least 10 years. Nine polymorphisms in six inflammasome genes were analyzed and multivariate association analyzes were performed to evaluate the association between the polymorphisms and CRC prognosis. Data showed that polymorphisms associated with a reduction in IL-18 levels (rs1834481, rs5744256) or an increase in activation of NLRP1 (rs12150220) and NLRP3 (rs35829419) inflammasome receptors were detrimental to the prognosis of CRC and may be used as prognostic markers.